Self- and Parent-Reported Fatigue 7 Years After Severe Childhood Traumatic Brain Injury: Results of the Traumatisme Grave de l'Enfant Prospective Longitudinal Study. Issue 2 (March 2020) - Câmara-Costa, Hugo; Francillette, Leila; Opatowski, Marion; Toure, Hanna; Brugel, Dominique; Laurent-Vannier, Anne; Meyer, Philippe; Dellatolas, Georges; Watier, Laurence; Chevignard, Mathilde
Abstract : Objective: To investigate presence of and factors associated with self- and parent-reported fatigue 7 years after severe childhood traumatic brain injury (TBI) in the prospective longitudinal study TGE ( Traumatisme Grave de l'Enfant —severe childhood trauma). Methods: Self-reports and/or parent reports on the Multidimensional Fatigue Scale were collected for 38 participants (aged 7-22 years) 7 years after severe childhood TBI, and 33 controls matched for age, gender, and parental educational level. The data collected included sociodemographic characteristics, age at injury and injury severity scores, overall disability (Glasgow Outcome Scale Extended), intellectual outcome (Wechsler scales), and questionnaires assessing executive functions, health-related quality of life, behavior, and participation. Results: Fatigue levels were significantly worse in the TBI than in the control group, especially for cognitive fatigue. Correlations of reported fatigue with age at injury, gender, TBI severity, and intellectual ability were moderate and often not significant. Fatigue was significantly associated with overall level of disability (Glasgow Outcome Scale Extended) and with all questionnaires completed by the same informant. Conclusion: High levels of fatigue were reported by 30% to 50% of patients 7 years after a severe childhood TBI. Reported fatigue explained more than 60% of the variance of reported health-related quality of life by the same informant (patient or parent).